(3fGA HjFI JYde bGFeI Ydi GdhGbY GdeYRR dJfejI egGQGJ GddZI GdYQHjI dOi JdGejP GdMdbI GdGHJOGFjI HHQfGeL GdHcGdhQjG GdOhdjI (B/s Remainder of title - (3QfG SejQ CMeO ZGdj,s; (3WGQb YHOGdefYe MLGRjs (2023)
(3gOa GdHMK GdMGdi Gdi HfGA HjFI JYde bGFeI Ydi GdhGbY GdeYRR hbjGS CKQgG ai JfejI egGQGJ GddZI GdeQFjI (B((3GdeTGgOI hGdYQV(B) (3ai GddZI GdYQHjI dOi JdGejP GdMdbI GdGHJOGFjI HCcGOjejI MjGI GdOhdjI HHQfGeL GdSfhGJ GdGHJOGFjI GdChdi, hJe GNJjGQ YjfI GdHMK YThGFjG ef YOO (B50 (3JdejP hJdejPI ef GdUa GdChd GdGHJOGFi hJbSjege YThGFjG Gdi eLehYJjf JLQjHjJjf eJSGhjJjf, MjK OQSJ GdeLehYI GdJLQjHjI GdGhdi HhGbY eYRR feGPL KdGKjI GdGHYGO ,HjfeG GdeLehYI GdKGfjI HhGbY eYRR HebGWY ajOjh, bO Je GSJNOGe fXGe EOGQI GdJYde (BMOODLE (3ceG Je GSJNOGe JWHjb (BEducate AR (3dfGA HjFI GdJYde deMhQ (B( (3Cjf fMf ai GdReGf hGdecGf(B)(3, hJe GdGYJeGO Ydi GdefgL THg GdJLQjHi, JchfJ COhGJ GdHMK ef GdGNJHGQ GdJMUjdi hHWGbI GdedGMXI, hJhUd GdHMK Gdi CKQ CSJNOGe cdG ef GdhGbY GdeYRR GdKdGKi GdGHYGO hGdajOjh ai GddZI GdYQHjI HTcd YGe, hNGUI GdCKQ GdGjLGHi dGSJNOGe JbfjI GdIGbY GdeYRR KdGKi GdGHYGO ai JfejI egGQGJ GddZI GdYQHjI dOiJdGejP GdUa GdGhd GdGHJOGFi HHQfGeL GdHcGdhQjG GdOhdjIs
The aim of this research is to build a learning environment based on augmented reality and to measure its impact on developing visual language skills in Arabic among students of the primary stage at Hayah academy International School in the Primary Years Program (PYP). Equally randomly assigned to two experimental groups, where the first experimental group studied with a 3D augmented reality, while the second experimental group studied with a video augmented reality, the Moodle learning management system was used, and the Educate AR application was used to build the learning environment for the unit of (3z(BWhere are we in time and place(3y(B, and it was relied on The quasi-experimental approach, the research tools consisted of the achievement test and the observation card, and the research found the effectiveness of using a three-dimensional augmented reality to develop Arabic language skills for first grade student in Elementary. s
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2023. s
(3HHdjhLQGajG(B: (3UaMGJ(B101-105.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGdEfLdjRjI(B.s
Keywords: (3JcfhdhLjG GdJYdjes; (3HQfGeL GdSfhGJ GdGHJOGFjI GdChdi (B(PYP).s -- (3egGQGJ GddZI GdYQHjI s -- (3HjFI JYde bGFeI Ydi GdhGbY GdeYRR s